PENGARUH PEMBINAAN DAN SOSIALISASI TERHADAP KEBERHASILAN PROGRAM KELUARGA BERENCANA PADA MASA PANDEMI COVID 19 DI KABUPATEN PESISIR BARAT - Jamal Jamal; Eka Suaib; Nyoto Setiyadhi (Universitas Bandar Lampung (UBL), 2021)
This study analyzes the effect of coaching and socialization on the success of the family planning program in the Pesisir Barat regency. This research was conducted with the aim of providing an overview of the success of the Family Planning Program in the midst of the Covid 19 Pandemic by using coaching and socialization methods that prioritize the use of technology to avoid crowds in accordance with health protocols and to provide answers to the formulation of existing problems. The author uses the theory of multiple linear regression because the independent variables consist of more than one. And that is directed to reveal the influence between the independent and dependent variables and test the significance of the influence between these variables. Thus it will be known to what extent the influence of the independent variables on the dependent variable.This research was conducted using quantitative research, with a quantitative descriptive approach / case study. Data collection in this study was obtained from questionnaires in Pesisir Tengah District in Pesisir Barat Regency.The result of the research is that the success of the Family Planning program during the Covid 19 Pandemic was influenced by coaching and socialization using online methods such as whatsapp groups and the operation of the Information Car. However, the frequency of coaching and socialization needs more attention because there is a very large influence on the decline in the success of the Family Planning Program during the Covid 19 Pandemic, so it is necessary to add both creativity to the use of animation in WhatsApp groups or additional budget for socialization using an Information car.